ACCOUNTING PROBLEMS OF PRICE CONTROL. - Kaulback, Frank S. (The Accounting Review, 1952)
Abstract To some groups, price stabilization is a matter of profit or loss and perhaps of adjustment within one business or industry. To the U.S. Office of Price Stabilization the subject is exceedingly complex. People must consider not just costs, profits or losses of a single group, but also their relationship to other businesses and industries, as well as to the nation as a whole. Now when Office of Price Administration (OPA) was set up, there was for most goods a general balance between supply and demand. There were sufficient unused production facilities to make supply quite sensitive to changes in demand. OPA's job, therefore, at first was merely to control the price of a few commodities whose demand was beginning to outrun supply because of defense requirements. Actually, this was not inflation control, but war cost control. The present emergency caught us at a time when there was very little slack in the economy to permit a self-adjusting between supply and demand. The sudden expansion of defense buying had an immediate effect upon prices.